Exploring fire safety awareness among the Malaysia Public / Azim Sulaiman , Mohd Najib Abd Rashid and Naim Mahyuddin - Sulaiman, Azim; Abd Rashid, Mohd Najib; Mahyuddin, Naim (2012)
As a global issue, fire incidents would cause severe implication(s)to victims. Fire incidents in Malaysia have increased rapidly over the years. Most cases of property loss involved residential buildings, causing severe injuries to victims. This scenario is of concern in terms of national development, because the prime purpose of owning a house is to provide shelter and security to the residents. In response to growing concerns, surveys were conducted over recent years, as shown in the media which revealed that the main contribution towards the increase of fire cases in Malaysia is due to a low level of fire safety awareness among the public. Furthermore, there is still a lack of fire safety measures especially in regards to landed residential properties. The installation of smoke detectors and portable fire extinguishers in houses in Australia, the United Kingdom and .ew Zealand, in comparison significantly reduced the fire fatalities and losses.Over recent years, there have been campaigns, seminars and trainings on fire safety conducted by the .ational Fire and Rescue Department of Malaysia throughout the nation. However, these fire preventive measures failed to increase the level of fire safety awareness among the public. Perhaps we should keep in mind the significant importance promoting fire safety awareness among the public. Does this responsibility solely rest with regulating authorities or with each individual?